Association of Fasting Blood Glucose and Glycated Haemoglobin with Some Markers of Oxidative Stress in Ile-Ife, Nigeria (Nigerian Journal of Health Sciences, 2023)
Background: Increased oxidative stress is a widely accepted contributor to the development and progression of diabetes mellitus (DM). A lot of work is being done to unravel the mechanisms linking oxidative stress with diabetes and its complications.Objective: The objective was to investigate the relationship between blood glucose levels, glycated haemoglobin and three markers of oxidative stress in DM: catalase (CAT), superoxide dismutase (SOD) and glutathione transferase (GST).Methods: Subjects were consecutive patients with Type 2 DM receiving treatment and apparently healthy controls. Fasting blood glucose, HbA1c, CAT, SOD and GST were assayed in the diabetic subjects and controls using standard procedures. Information on the presence of neuropathy and nephropathy was obtained from case notes, whereas screening for retinopathy was carried out at the Ophthalmology Unit of Obafemi Awolowo University Teaching Hospitals Complex. Data were analysed using Statistical Package for the Social Sciences for Windows, version 17.Results: A total of 115 subjects comprising 65 diabetics and 50 controls were studied. Mean fasting blood glucose, CAT, SOD and GST activities in test and control subjects were 9.12 (0.48) and 4.78 (0.63) mmol/L, 48.20 (2.69) and 63.22 (1.83) units/mg, 53.22 (2.44) and 62.55 (2.68) units/mg and 1.35 (0.09) and 3.47 (0.11) units/mg, respectively. Statistically significant differences were observed when levels of fasting blood sugar, CAT, SOD and GST were compared between diabetic and non‑diabetic subjects. Diabetic subjects with one or more microvascular complications were found with significantly higher HbA1c levels than those without apparent complication. There was significant negative correlation between fasting blood glucose and all three antioxidant enzymes.Conclusion: The results of the present study suggested that fasting blood sugar modulated levels of antioxidant enzymes while protein glycation plays a role in the development of microvascular complications.